The villa - Roberts, Nora (New York : G. P. Putnam's Sons, 2001)
The top PR executive for the family winery, Sophia Giambelli finds her life turned upside down by the merger with the MacMillan family's winery and her powerful attraction to professional rival Tyler MacMillan.
Keywords: Wine and wine making -- Fiction; Love stories